1967
DOI: 10.1128/aem.15.2.249-256.1967
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Inactivation of Type E Botulinum Toxin1

Abstract: The theoretical required cooking times for inactivation of type E Clostridium botulinum toxin (5,000 LD5o mouse units per 0.5 ml) in haddock fillets of various sizes were calculated by graphical integration of the toxin inactivation rate and heat penetration data. The results indicated that normal cooking procedures should suffice to inactivate this amount of toxin. This conclusion was substantiated by the following additional experimental observations which revealed that the original experiments had been cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

1969
1969
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 3 publications
3
2
0
Order By: Relevance
“…minutes at 71°C, 5-35 minutes at 74°C, and a maximum of 5 minutes at 85°C. As has been reported previously, toxicity remained longer if the original levels were higher (Scott andStewart, 1950, andLicciardello et al, 1967).…”
Section: Figuresupporting
confidence: 70%
See 2 more Smart Citations
“…minutes at 71°C, 5-35 minutes at 74°C, and a maximum of 5 minutes at 85°C. As has been reported previously, toxicity remained longer if the original levels were higher (Scott andStewart, 1950, andLicciardello et al, 1967).…”
Section: Figuresupporting
confidence: 70%
“…encing heat stability were not held constant. In our tests, the type E toxin was considerably more stable than reported by Ohye and Scott (1957); Licciardello, Nickerson, Ribich, and Goldblith (1967); and Yao, Denny, and Bohrer (1973).…”
Section: Figuresupporting
confidence: 52%
See 1 more Smart Citation
“…Similar experiments aiming at determining the relation between the oral and intraperitoneal lethal doses of Clostridium botulinum type E toxin in mice have been performed by Licciardello et al (1967). They found that the oral lethal dose was 50--100 times greater than the intraperitoneal dose, and this corresponds fairly well with the results obtained in these experiments.…”
Section: Discussionsupporting
confidence: 76%
“…The pathogen is relevant for chilled foods under reduced oxygen packaging (ROP), in particular foods of the RePFED category that have not been processed to eliminate the spores (see Section 3.2.1.2) or the physico‐chemical characteristics do not inhibit their growth (see Section 3.2.2) (Notermans et al., 1990; Peck, 1997; FSA 2017). Compared to other bacterial toxins, those of non‐proteolytic C. botulinum can be heat inactivated by normal food cooking procedures (Licciardello et al., 1967; Wachnicka et al., 2016).…”
Section: Assessmentmentioning
confidence: 99%